Analisis Yuridis Pelanggaran Hak Cipta PT Metro Hotel Internasional Semarang (Studi Putusan:43PK/Pdt.Sus-HKI/2017) - Sifa Fauziah; Budi Santoso (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractInter Sprot Marketing Company (ISM Company) filed a lawsuit at the Semarang Commercial Court. At the judicial review level, the Panel of Judges at the Supreme Court stated that the Defendant was proven to have committed an illegal act in the form of copyright. There needs to be a juridical study of the judges' considerations in adjudicating copyright cases between ISM Company and Metro Hotel Internasional Semarang Company at the Judicial Review level. The approach method that will be used by the writer is normative juridical and comparative study. The results of the discussion of the problem are 1) The basis for the consideration of the Supreme Court Council on the Judicial Review Decision is in accordance with Law Number 28 of 2014 concerning Copyright, because world broadcasts are included in the category of cinematographic works, so they are automatically protected by copyright. 2) The World Cup broadcast is a cinematographic work based on Article 40 paragraph (1) letter m of Law Number 28 of 2014 concerning Copyright.Keywords: decision; supreme court; copyrightAbstrakPT Inter Sprot Marketing (PT ISM) mengajukan gugatan ke Pengadilan Niaga Semarang. Pada tingkat Peninjauan Kembali, Majelis Hakim Mahkamah Agung menyatakan bahwa Tergugat terbukti sudah melakukan perbuatan melawan hukum berupa pelanggaran hak cipta Perlu adanya kajian yuridis terhadap pertimbangan majelis hakim dalam mengadili perkara pelanggaran hak cipta antara PT ISM dengan PT Metro Hotel Internasional Semarang pada tingkat PK. Metode pendekatan yang akan digunakan Peneliti adalah pendekatan yuridis normative dan studi komparatif. Hasil pembahasan permasalahan adalah 1) Dasar pertimbangan Majelis Mahkamah Agung pada Putusan Peninjauan Kembali dinilai sudah sesuai dengan Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta, karena tayangan siaran piala dunia masuk dalam kategori karya sinematografi, sehingga secara otomatis dilindungi oleh hak cipta. 2) Tayangan siaran Piala Dunia merupakan karya sinematografi berdasarkan Pasal 40 ayat (1) huruf m Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta.Kata kunci: putusan; mahkamah agung; hak cipta